2020
DOI: 10.1038/s41598-020-72538-x
|View full text |Cite
|
Sign up to set email alerts
|

Omidenepag, a non-prostanoid EP2 receptor agonist, induces enlargement of the 3D organoid of 3T3-L1 cells

Abstract: 2D and 3D cultures of 3T3-L1 cells were employed in a study of the effects of Omidenepag (OMD), interacting with a non-prostanoid EP2 receptor, on adipogenesis. Upon adipogenesis, the effects on lipid staining, the mRNA expression of adipogenesis-related genes (Pparγ, CEBPa, Ap2, and Glut4) and the extracellular matrix (ECM) including collagen type 1, 4 and 6, and fibronectin, and the size and physical property of 3D organoids were compared between groups that had been treated with EP2 agonists (butaprost and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 36 publications
15
59
0
Order By: Relevance
“…To compare effects of FP-Rag, BIM-A, and EP2 agonist on physical property of the 3D HOFs organoid, changes of their sizes were evaluated. Similar to the 3T3-L1 cells, 14 , 18 uniform round-shaped 3D organoids were obtained from 20,000 HOFs cells ( Fig. 1 A).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…To compare effects of FP-Rag, BIM-A, and EP2 agonist on physical property of the 3D HOFs organoid, changes of their sizes were evaluated. Similar to the 3T3-L1 cells, 14 , 18 uniform round-shaped 3D organoids were obtained from 20,000 HOFs cells ( Fig. 1 A).…”
Section: Resultssupporting
confidence: 67%
“… 2 , 11 , 14 Furthermore, our recent pilot study indicated that OMD induced different effects toward 3T3-L1 cells as compared to BIM-A. 18 This prompted us to perform a similar study based on 3D organoid cultures using HOFs rather than 3T3-L1 cells to determine the effects of OMD on human orbital fatty tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this current study was to evaluate the effects of ROCK-is toward adipogenesis and ECM expression in 3T3-L1 cells. In our previous studies, we found that the effects of PGF2α agonists and EP2 agonists on adipogenesis as well as the expression of ECM in 3T3-L1 cells were significantly different between their 2D and 3D cultures 22 , 24 , and the findings suggested that 3D cultures may become a reliable ex vivo model for use in this research field. However, our 3D drop-culture method has not yet fully characterized so far, especially in terms of the physical properties, sizes and stiffness of organoids during the period of their culture.…”
Section: Resultsmentioning
confidence: 91%
“…Oil Red O lipid staining of the 2D cultured 3T3-L1 cells and BODIPY lipid staining of the 3D 3T3-L1 organoids were performed as described previously 24 . To quantify their staining levels, measurements of optical density of the extracted Oil Red O dye, and the fluorescence intensity of the BODIPY-stained lipid droplets were used, respectively 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation